Rekonstruksi Asuransi Jiwa Syariah: Telaah Hadis tentang Transparansi dan Amanah dalam Jual Beli - Aldi Munazri Rambe (Yayasan Albahriah Jamiah Indonesia, 2025)
The implementation of life insurance in the context of Islam requires a deep understanding of the principles of transparency and trust in buying and selling. The background of this study focuses on how the hadiths of the Prophet can be a guide in developing a strategy for implementing life insurance that is in accordance with Islamic teachings. The purpose of this study is to examine the relevance of the principles of transparency and trust contained in the hadith to the practice of life insurance, as well as to provide recommendations for implementation in accordance with Islamic ethics. The research method used is an in-depth literature study of the hadiths related to buying and selling and insurance transactions, coupled with a comparative analysis of modern life insurance practices. The results of the study indicate that the principles of transparency in contracts and trust between the parties involved are key to formulating life insurance policies that are in accordance with Islamic law. The discussion includes the application of these principles in life insurance contracts to ensure that the insurance products offered do not violate Islamic teachings and function as a form of fair and transparent protection for all parties.